Description of the female terminalia of twenty species of Proconiini (Hemiptera: Cicadellidae) from Argentina - Dellapé, Gimena (Zootaxa, 2015)
The tribe Proconiini is represented in Argentina by 18 genera and 44 species. Characters for the identification of most genera and species are from male specimens, while females are identified by association with males. In this contribution, the female terminalia of 20 species of Proconiini from Argentina are described and illustrated. The value of each character to genus or species identification is discussed.